Powers of attorney, vulnerable adults and Private international law: some reflections - Guzmán Zapater, Mónica (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The powers of attorney granted by vulnerable people are part of the new framework designed by Law 8/2022 as a voluntary support measure and in the perspective of ratification of the 2000 Hague Convention on the Protection of Adults, which improves and therefore changes the regulation contained in articles 9.6.2. and 10.11 of the Civil Code.